Technical product documentation - Lettering : - International Organization for Standardization
This part of ISO 3098 specifies the Latin alphabet, numerals and marks for use on technical drawings and associated documents. It primarily concerns letters written with the aid of stencils, but is equally applicable to freehand lettering or other appropriate methods